Experimental study of dynamic deformation structuredmedium under the impulse loading - S. V. Mykulyak; V. O. Polyakovskiy (Геофизический журнал, 2014)
Experiments on deformation structured model medium formed by elements in the form of balls of the same diameter under the impulse loading are performed. It is found that the stress-strain diagram of such medium depends on the size of structure elements and the nature of their interaction. The character of deformation of the structured medium by multiple loads is investigated.